2021
DOI: 10.1186/s12905-021-01333-1
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the factors affecting sexual violence against women in Turkey: a population-based analysis

Abstract: Background Sexual violence is one of the most investigated types of violence by national and international decision makers. The purpose of this study was to detect the factors that affect sexual violence against women in Turkey. Methods In this study, a cross-sectional data set was employed from the survey titled the National Research on Domestic Violence against Women in Turkey, which was conducted by the Hacettepe University Institute of Populati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 47 publications
1
26
1
Order By: Relevance
“…According to these results, participants whose partners declared to have a high income were subjected to invisible violent behaviors more often. Although these results differ from those of previous studies [ 80 , 81 ], our findings are in line with the resource theory of power and its relationship with the theory of patriarchal norms [ 56 ]: if men earn more money, they will have more power within the relationship. Nevertheless, it is important to highlight that although the socioeconomic level of women and their partners is a key factor to take into account when designing interventions for the prevention and detection of IPV, some authors urge us to also focus on other cultural aspects, gender attitudes, and inequalities [ 82 , 83 ], which define the norms and values that govern interpersonal relationships [ 61 , 84 , 85 ].…”
Section: Discussionsupporting
confidence: 51%
“…According to these results, participants whose partners declared to have a high income were subjected to invisible violent behaviors more often. Although these results differ from those of previous studies [ 80 , 81 ], our findings are in line with the resource theory of power and its relationship with the theory of patriarchal norms [ 56 ]: if men earn more money, they will have more power within the relationship. Nevertheless, it is important to highlight that although the socioeconomic level of women and their partners is a key factor to take into account when designing interventions for the prevention and detection of IPV, some authors urge us to also focus on other cultural aspects, gender attitudes, and inequalities [ 82 , 83 ], which define the norms and values that govern interpersonal relationships [ 61 , 84 , 85 ].…”
Section: Discussionsupporting
confidence: 51%
“…This is consistent with the findings from the NDHS 2016 which found that sexual violence increased with age among women [ 6 ]. However there are studies from countries like Turkey and US, from before the pandemic, that contradicts these findings and find an opposite trend of association [ 42 , 43 ]. These studies found that the prevalence of violence decreased with age.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies highlighted previous violence exposure as a risk factor for exposure to violence. Alkan and Tekmanlı 2021 reported that women who had suffered physical, economic, or verbal abuse had an increased likelihood of being exposed to sexual violence. According to Fisher 2004 , childhood victimization increased women's chances of being victimized in high school and put women at risk for different types of dating violence.…”
Section: Discussionmentioning
confidence: 99%